The Nutrition Counseling Improve Volleyball Athelets Knowledge - Permadi, M Rizal; Purnasari, Galih; Renamastika, Stephani Nesya (International Journal of Healthcare and Information Technology, 2024)
The dietary intake of athletes is crucial for attaining peak performance, sustaining physical fitness, preventing the risk of injury, and speeding post-competition recovery. A prevalent issue among athletes is insufficient food consumption relative to their nutritional requirements, resulting from a limited understanding of proper dietary practises. The objective of this study is to increase athletes' understanding of dietary consumption through the provision of nutritional guidance to athletes. The study was conducted on ten volleyball atheletes who were in the process of training for the PORPROV (Pekan Olahraga Provinsi) Jawa Timur VIII tournament in 2023. This research used the pre-experimental design method . The research design uses one group pre-test post-test design. The data collected includes body weight, height, food intake and nutritional knowledge of athletes. The analysis used a one sample t-test to see the athletes' food intake and knowledge before and after being given nutritional counseling. The results of this study were a significant increase in athletes' knowledge and energy intake (p <0.05), the average athlete knowledge score before nutritional counseling was 52.5 and after nutritional counseling it was 74.5. The mean energy consumption before to receiving nutritional counselling was 1794.6 kilocalories (kcal), while after receiving nutritional counselling, it increased to 2141.8 kcal. Providing nutrition counselling to volleyball athletes can improve their understanding of dietary requirements and improve their food consumption, finally leading to optimal performance. The government should provide nutritional counseling services for athletes